2021
DOI: 10.1002/bab.2250
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and antifungal activity of Bacillus cereus strain NK91 chitinase from rhizospheric soil samples of Himachal Pradesh, India

Abstract: Newly isolated Bacillus cereus strain NK91 was characterized for extracellular chitinase production. Partially purified chitinase showed a molecular weight of 43.7 kDa in SDS-PAGE analysis. The optimum pH and temperature for the partially purified enzyme were 7.0 and 40 • C, respectively. The addition of Mn 2+ resulted in a 21% increase in enzyme activity as compared to the control. The V max and K m of the enzyme were determined as 76.9 μmol/min and 0.07 mg/mL, respectively. This enzyme exhibited stronger ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Differences in these optimum temperature activity responses between soils may be due to differences in microbial composition (and thus microbialproduced chitinase isozymes) between soils. Optimum temperatures varying between 40 and 60 • C have been recorded for chitinases (partially) purified from soil microorganisms (Gao et al, 2008;Alster et al, 2016;Du et al, 2021;Thakur et al, 2021). Additionally, soil-type-dependent stabilization of enzyme structure against thermal denaturation through interaction with soil surfaces might also mediate differential temperature responses (Sarkar et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in these optimum temperature activity responses between soils may be due to differences in microbial composition (and thus microbialproduced chitinase isozymes) between soils. Optimum temperatures varying between 40 and 60 • C have been recorded for chitinases (partially) purified from soil microorganisms (Gao et al, 2008;Alster et al, 2016;Du et al, 2021;Thakur et al, 2021). Additionally, soil-type-dependent stabilization of enzyme structure against thermal denaturation through interaction with soil surfaces might also mediate differential temperature responses (Sarkar et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Thakur et al [5] also showed that, after incubation together, antifungal activity of B. cereus strain NK91 chitinase was determined against F. oxysporum, R. solani, and C. gloeosporioides. All the results of those studies conclude that, because of the differences of the chemical structures of the fungal chitins, chitinolytic activities also varies as a result of the subsite structure in the enzyme binding cleft.…”
Section: Discussionmentioning
confidence: 99%
“…Thakur et al, [5] purify and characterize extracellular chitinase from B. cereus NK91 and then to test the partially puri ed enzyme for its antifungal activity against some phytopathogens. They add different concentrations of partially puri ed chitinase into warm molten PDA and after solidi ed, 5-day old agar mycelial plugs of fungi were plated on enzyme-including media.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in these optimum temperature-activity responses between soils may be due to differences in microbial composition (and thus microbial-produced chitinase isozymes) between soils. Optimum temperatures varying between 40 °C and 60 °C have been recorded for chitinases (partially) purified from soil microorganisms (Gao et al, 2008;Alster et al, 2016;Du et al, 2021;Thakur et al, 2021). Additionally, soil-type dependent stabilization of enzyme structure against thermal denaturation through interaction with soil surfaces might also mediate differential temperature responses (Sarkar et al, 1989).…”
Section: Discussionmentioning
confidence: 99%